Analysis of Needs for the Development of Local Wisdom-Based Junior High School Science E-Modules Related to Ethnoscience in South Sumatera - Yuliana Yuliana; Apit Fathurohman; Sardianto Markos Siahaan (Postgraduate, University of Mataram, 2023)
This article aims to present the results of an analysis of the needs of local wisdom-based e-module teaching materials related to ethnoscience in South Sumatera. The data in this article were collected by distributing a questionnaire with the help of a Google form which was filled in by 35 science teachers and 69 students in grades VIII and IX at SMPN 1 Madang Suku I, even semester of the 2022/2023 school year, and then analyzed using descriptive analysis. The objects of study in this article include the suitability of KI and KD, the teaching materials used by teachers, and the needs of teachers and students for local wisdom-based e-modules related to ethnoscience in South Sumatera. The results of the study show that 100% of teachers use other handbooks and other teaching materials that are in accordance with KI and KD; 56.3% of teachers use special teaching materials other than books from schools to assist in understanding a material; 100% of teachers need e-module teaching materials based on local wisdom related to ethnoscience in South Sumatera which can be used to study material on liquid pressure; 23.2% of students have handbooks other than science books that are borrowed from the school; 92.8 Students look for other materials to help understand the science material; and 95.7% of students need e-module teaching materials based on local wisdom related to ethnoscience so that the subject matter is more interesting and easier to understand. Thus, it can be understood that e-module teaching materials based on local wisdom related to ethnoscience in South Sumatera are needed to make it easier for students to understand the material.